Comparing the effect of two different interfaces on breathing of preterm infants at birth: A matched-pairs analysis. (December 2020) - Kuypers, Kristel L.A.M.; Lamberska, Tereza; Martherus, Tessa; Dekker, Janneke; Böhringer, Stefan; Hooper, Stuart B.; Plavka, Richard; te Pas, Arjan B.
Abstract: Objective: Applying a face mask could provoke a trigeminocardiac reflex. We compared the effect of applying bi-nasal prongs with a face mask on breathing and heart rate of preterm infants at birth. Methods: In a retrospective matched-pairs study of infants <32 weeks of gestation, the use of bi-nasal prongs for respiratory support at birth was compared to the use of a face mask. Infants who were initially breathing at birth and subsequently received respiratory support were matched for gestational age (±4 days), birth weight (±300 g), general anaesthesia and gender. Breathing, heart rate and other parameters were collected before and after interface application and in the first 5 min thereafter. Results: In total, 130 infants were included ( n = 65 bi-nasal prongs, n = 65 face mask) with a median (IQR) gestational age of 27 +2 (25 +3 –28 +4 ) vs 26 +6 (25 +3 –28 +5 ) weeks. The proportion of infants who stopped breathing after applying the interface was not different between the groups (bi-nasal prongs 43/65 (66%) vs face mask 46/65 (71%), p = 0.70). Positive pressure ventilation was given more often when bi-nasal prongs were used (55/65 (85%) vs 40/65 (62%), p < 0.001). Heart rate (101 (75–145) vs 110 (68–149) bpm, p = 0.496) and oxygen saturation (59% (48–87) vs 56% (35–84), p = 0.178) were similar in the first 5 min after an interface was applied in the infants who stopped breathing. Conclusion: Apnoea and bradycardia occurred often after applying either bi-nasal prongs or a face mask on the face for respiratory support in preterm infants at birth.